Investigating the Effect of Recycled Polymers application on bed Soil Quality of sanitary Landfills and Groundwater Pollution Control - Mostafa Mohammadnejad Araei; hamidreza Nassehinia; Yousef Dadban Shahamat; Mohammad Ali Zazouli (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: One of the important problems in the management of waste is the health and environmental hazards of the leachate leakage of urban waste landfills to groundwater. This research aimed to investigate the improvement of the landfill properties using recycled polymer. Methods: In this study, PET: Polyethylene Terephthalate and clay were mixed with the ratio of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1 wt%. Moreover, Moreover, its effect on the quality parameters of clay, including consolidation, settlement, shear stress, adhesion, and infiltration were determined in soil mechanics laboratory located in the city of Gorgan. All experiments were conducted based on American Society for Testing and Materials. Results: Results showed that the internal friction angle in clay and clay composed with polymer were 20.93 wt% and 30.3 wt%, respectively. Moreover, the compaction of clay decreased from 0.163 g/cm2 to 0.110 g/cm2. Permeability results showed that the use of PET decreased the  permeability of soil from 1.82 E-3cm/min to 1.57 E-3cm/min. Conclusion: The use of recycled polymer can improve the soil conditions of landfills in terms of permeability and resistance to leaching, which could reduce the volume and the recycling process of waste. Moreover, this issue contribute to the quality and strength of the substrate to prevent environmental contamination as well as groundwater polution.